2000
DOI: 10.1086/301448
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Radio Maps of Wolf-Rayet Galaxies: Optically Thick H [CSC]ii[/CSC] Regions?

Abstract: We present 20, 6, 3.6, and 2 cm Very Large Array maps and continuum-free Ha images of nine WolfRayet galaxies. The radio maps were made with high spatial resolution to reject extended emission and to emphasize the star formation regions. The ratio of Ha to radio is at least a factor of 10 lower than predicted, indicating that the radio emission is from highly obscured sources. We map the radio spectral index, a across each galaxy. In all the sample galaxies except one, the radio spectrum is much (S l P la), Ña… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 30 publications
9
90
1
Order By: Relevance
“…If the beam is not centered on the galaxy (in the case of unresolved galaxies) or is not centered on a bright knot of emission (in the case of resolved galaxies), the smaller beams could contain even less flux than would be expected after corrections for the beams' areas. NGC 1741 and NGC 4490 are likely affected by pointing offsets, as seen by comparing the GBT pointing in Table 1 to previous radio continuum maps in Figure 2 of Beck et al (2000) and Figure 4 of Aversa et al (2011). As described in Section 2.2, pointing offsets from the peak of radio continuum emission result in the need for larger beam correction factors than derived from the archival radio continuum data, the lack of which result in steep spectra at the observed frequencies.…”
Section: Galaxies With Steep Radio Spectramentioning
confidence: 88%
See 1 more Smart Citation
“…If the beam is not centered on the galaxy (in the case of unresolved galaxies) or is not centered on a bright knot of emission (in the case of resolved galaxies), the smaller beams could contain even less flux than would be expected after corrections for the beams' areas. NGC 1741 and NGC 4490 are likely affected by pointing offsets, as seen by comparing the GBT pointing in Table 1 to previous radio continuum maps in Figure 2 of Beck et al (2000) and Figure 4 of Aversa et al (2011). As described in Section 2.2, pointing offsets from the peak of radio continuum emission result in the need for larger beam correction factors than derived from the archival radio continuum data, the lack of which result in steep spectra at the observed frequencies.…”
Section: Galaxies With Steep Radio Spectramentioning
confidence: 88%
“…T72 denotes galaxies that were observed, but not detected, by Tovmassian (1972) at 9.5 mm (31.6 GHz). T94 (Turner & Ho 1994), B00 (Beck et al 2000), B02 (Beck et al 2002), B03 (Beswick et al 2003), C04 (Chyży & Beck 2004), J04 (Johnson et al 2004), L04 (Lisenfeld et al 2004), R05 (Rosa-González 2005), T06 (Tsai et al 2006), B07 (Beck et al 2007), R08 (Reines et al 2008), J09 (Johnson et al 2009), D11 (Dumas et al 2011), K11 (Kodilkar et al 2011), and A11 (Aversa et al 2011) denote galaxies that were observed at lower frequencies. The galaxies are described in more detail in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…Then the radio spectrum can be fit by models of homogeneous, isothermal, dust-free, ionization bounded regions of ionized gas, to obtain the turnover frequency ν t , the EM, n e , and infer the size D of the region (e.g., Deeg et al 1993;Johnson et al 2001;Hunt et al 2004). Alternatively, the optically thick and optically thin regions of the radio spectrum can be separated to constrain ν t , and thus infer the emission measure EM, size D, and rms electron density n e (e.g., Gordon 1988;Beck et al 2000).…”
Section: Extragalactic Radio Data Setsmentioning
confidence: 99%
“…Narrowband imaging may also be important to track the faintest youngest members of the population, which may not be detected with broadband IR imaging, although they are bright in narrow filters tuned to the recombination lines of their HIIRs (AlonsoHerrero et al 2002). Radio and mid-IR observations have uncovered still more heavily embedded regions of massive star formation that are heavily obscured even at 2 m (e.g., Kobulnicky & Johnson 1999;Beck et al 2000Beck et al , 2001Vacca et al 2002;Cabanac et al 2005); these objects are very young, dense, compact HIIRs that are the massive analogs of ultracompact H ii regions (UCHIIs). Hence they are dubbed ultradense HIIRs, or UDHIIs, by Kobulnicky & Johnson (1999), and they are the supposed precursors of optically visible SSCs.…”
Section: Introductionmentioning
confidence: 99%